Memahami Sejarah Intelektual Isaiah Berlin (1909-1997) - Kamaruzzaman Bustamam; Ahmad Ahmad (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
This article aims to examine the biography of Isaiah Berlin (1909-1997), a philosopher from Oxford University. Berlin is a thinker who against the Enlightenment, which he made several criticisms to Western thought. To do this, he has produced some written works that edited by Henry Hardy. The editor has contributed to introduce the ideas of Berlin to the West. This study is an introduction on Berlin by looking his works and his intellectual foundations. Finally, it is argued that Berlin has authored many works and using the analytical philosophy as his intellectual foundations.[Artikel ini berupaya untuk menyajikan tentang biografi Isaiah Berlin (1909-1997), salah seorang filosof dari Oxford University. Berlin merupakan salah satu pemikir yang melakukan anti terhadap Era Pencerahan dimana dia melakukan kritikan terhadap pemikiran Barat. Untuk melakukan hal tersebut, dia telah menghasilkan berbagai karya yang hampir semuanya diedit oleh Henry Hardy. Editor ini telah berjasa di dalam memperkenalkan gagasan-gagasan Berlin di Barat. Karya ini merupakan pengantar terhadap Berlin dengan melihat karya-karyanya dan fondasi intelektualnya. Akhirnya, dapat dikatakan bahwa Berlin telah menghasilkan berbagai karya melalui pendekatan filsafat analitik.]